Fabrication of Mesoporous Titanium Dioxide Assisted by Resorcinol/Formaldehyde Gel - Mananya Thovicha; Varong Pavarajarn (ASEAN Journal of Chemical Engineering, 2011)
Mesoporous structures of materials have attracted considerable attention recently because of their potential in a variety of applications. In this work, resorcinol/formaldehyde (RF) gel was used as a template for the synthesis of mesoporous titania, which is in great interest in catalysis, photocatalysis, gas sensor and photovoltaic applications. RF-gel was prepared by the sol-gel polycondensation of resorcinol (R) and formaldehyde (F). Titanium tetraisopropoxide (TTIP) was used as precursor for titania. However, direct incorporation of TTIP into RF-gel was limited by a spontaneous reaction between TTIP and RF gel, which consequently resulted in rapid solidification of the gel. Titania sol was firstly prepared from TTIP via sol-gel process. After certain period of aging time, the titania sol was added into RF mixture, which had been aged for predetermined period of time as well. After that, the mixture was further aged for another 36 hours before being dried at 80°C. Finally, the dried gel was calcined at 500°C for 4 hours to remove the RF template. The obtained titania powders were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), surface area measurement via nitrogen adsorption, and Fourier transform infrared spectroscopy (FTIR). The specific surface area of the samples was in the range of 30-33 m2/g. and the average diameter of about 8.8-37.7 nm. It was found that the rate of addition for titania sol into the RF-gel had influence on the phase of the final product. The increased rate favored the formation of titania in rutile phase.